Strategic Efforts to Enhance the Mudharabah Financing Portfolio at PT Bank Sumut Syariah Medan through the Analytic Network Process (ANP) Approach - Ririn Anjani Rangkuti; Yenni Samri Juliati Nasution; Tuti Anggraini (Universitas KH. Abdul Chalim Mojokerto, 2025)
Islamic banking in Indonesia has experienced rapid growth in recent years, in line with the increasing public awareness of fair and sustainable Islamic economic principles. The mudharabah contract, as one of the core profit-sharing products in Islamic banking, holds significant potential in supporting real sector financing, particularly for MSMEs. However, data from PT Bank Sumut Syariah for the 2019-2023 period indicates a declining trend in the proportion of mudharabah financing, reflecting strategic challenges such as moral hazard risks, information asymmetry, and the bank’s preference for lower-risk contracts like murabahah. This study aims to formulate strategies to enhance the mudharabah financing portfolio at PT Bank Sumut Syariah in Medan using the Analytic Network Process (ANP) method. Data were collected through in-depth interviews with experts, regulators, and practitioners involved in mudharabah financing. The findings reveal that the factors contributing to the fluctuation and relatively low share of mudharabah financing compared to other contracts are divided into two main aspects: internal and external. To address these challenges, one effective solution is to provide training for MSME actors to improve their skills and capabilities. The top priority strategies include: maximizing the implementation of mudharabah, strengthening the capital portfolio, accurate market segmentation, establishing a risk guarantee institution, conducting education and outreach programs, and fostering partnerships with external mentoring organizations.